Pengaruh Bauran Komunikasi Pemasaran Terhadap Proses Keputusan Pembelian Konsumen Provider Tri di Kota Denpasar - Novita Devi, Ida Ayu Chandra Surya; Giantari, I Gusti Ayu Ketut (E-Jurnal Manajemen; Vol 3 No 7 (2014), 2014)
This research aims to determine the effect of the marketing communications mix to consumer buying decision process tri provider in the city of Denpasar. Analysis of the data used is a descriptive analysis, multiple linear regression analysis with factor analysis. The results analysis coefficient of determination (R 2 ) unknown amount of 0.648. It shows that 64,8% of variation changes the variable rise and fallvariables change consumer buying decision process is influenced by the marketing communication mix variables, while the remaining 39,2% is influenced by other variables not included in the model. The results of this study showed a significant effect simultaneously and partially between the marketing communications mix to consumer buying decision process Tri provider in the city of Denpasar.. Normal 0 false false false EN-US X-NONE X-NONE
Keywords: Marketing Communications, Consumer Buying Descision Process